Livelihood-management: Lessons from Bhagavad Gita - Dr. Anu Gupta; Puneet Jain (Innovative Research Thoughts, 2024)
In today’s volatile business environment, being effective is the hallmark of a good manager. An effective manager must achieve such a level of excellence and effectiveness that it sets him apart from those whom he is managing. The Bhagavad Gita has 700 verses (Slokas) written in 18 chapters talks not just about the spiritual enlightenment but teach us on all the managerial techniques that can be applied by the managers like leadership, motivation, quality in work, goal setting, decision making, and planning. The Bhagavad Gita was delivered in the battlefield Kurukshetra by Lord Sri Krishna to Arjuna as a counselling to do his duties, to boost Arjuna’s declining morale, motivation and to take the Arjuna out of the intra-personal conflict. Arjuna got mentally depressed when he saw his relatives with whom he has to fight. Bhagavad Gita has got all the management tactics to achieve the mental equilibrium and to overcome any crisis situation.